Analisis Nilai Tambah Produk Olahan Manggis Di Kelompok Wanita Tani Sri Lestari Desa Somongari Kecamatan Kaligesing Kabupaten Purworejo - Nur Fajriyah; Uswatun Hasanah; Dyah Panuntun Utami (Jurnal Riset Agribisnis dan Peternakan, 2019)
The purpose of this study 1) the process of making mangosteen peel tea, pure mangosteen peel powder, instant mangosteen peel powder, mangosteen peel powder capsules, and mangosteen fruit juice in Somongari village, Kaligesing district, Purworejo district, 2) the magnitude of the added value of processed mangosteen skin powder into mangosteen skin powder mangosteen, mangosteen peel capsules, pure mangosteen peel powder, instant mangosteen peel powder and mangosteen juice in the Sri Lestari Farmer Women's Group Somongari Village Kaligesing District Purworejo District. The research method used was a case study, data were analyzed using descriptive analysis. A sample of 5 people consisted of key informants and ordinary informants. Value-added analysis using the Hayami Method. The results showed that the process: 1) Mangosteen skin tea is fresh mangosteen then split (take the skin), washed, chopped, dried, sorted and finally packaged (packaged), 2) Mangosteen skin capsules are fresh mangosteen (take soft skin), washed, dried, grinded, sifted, put the powder into capsules and finally packaged, 3) Mangosteen skin pure powder that is fresh mangosteen split (take soft skin), washed, dried, ground, sifted, sifted and packaged (packaged), 4) Instant skin powder mangosteen, namely fresh mangosteen (take soft skin), washed, dried, ground, sifted, cooked powder with added brown sugar and water to form crystals and finally packing (packing), 5) Mangosteen juice namely mangosteen freshly washed, split take meat fruit and separate seeds, boiling (cocktail) then blender and boil back to the last packing. The added value of mangosteen skin tea is IDR 32,177.03, mangosteen skin capsule is IDR 315,190.96, pure mangosteen skin powder is IDR 64,598.85, instant mangosteen skin powder is IDR 72,484.21 and mangosteen juice is IDR 37,926.81.